1990
DOI: 10.2135/cropsci1990.0011183x003000050028x
|View full text |Cite
|
Sign up to set email alerts
|

Sink Manipulation in Wheat: Compensatory Changes in Kernel Size

Abstract: Kernel size (KS), an important yield component of wheat (Triticum aestivum L.), depends on assimilate availability and the capacity of the kernel to use assimilates. The objective of this study was to evaluate the response of wheat cultivars with different KS (20 to 43 mg kernel −1,) to sink manipulation. Twenty cultivars grown at two locations were partially degrained by removal of all spikelets from one side of only one spike per plant. Control spikes were left intact. Partial degraining decreased kernel num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In this study, JN17, DF611, GY503, TA9818, HN341 and SJZ8 may be source limited cultivars, YN15, S7221 and W62036 may be sink limited cultivars. However, in no case was the compensation by increased grain weight sufficient to achieve the total grain weight of the intact plant (Ma et al 1990). Borrá s et al (2004 also showed growth of wheat grains is apparently more sink-than sourcelimited under most conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, JN17, DF611, GY503, TA9818, HN341 and SJZ8 may be source limited cultivars, YN15, S7221 and W62036 may be sink limited cultivars. However, in no case was the compensation by increased grain weight sufficient to achieve the total grain weight of the intact plant (Ma et al 1990). Borrá s et al (2004 also showed growth of wheat grains is apparently more sink-than sourcelimited under most conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Although high temperatures during this period produced high grain growth rates, they also induced to a shorter duration of grain filling period which finally determined a lower final grain weight (WARRINGTON et al 1977, BRUCKNER and FROHBERG 1987, GON-ZALEZ MoNTANER 1987. Other authors (GRABAU et al 1990, MA et al 1990) have reported that reducing the number of grains withm a spike, some cultivars produced partial compensatory increases in individual grain weight but some others did not. This genotypic variation could be related to the cultivar potential for formating A starch granules during the first period of grain filling (MARTINEZ-CARRASCO et al 1988).…”
Section: Introductionmentioning
confidence: 93%
“…However, it has been rencently reported that in some modern cultivars wheat yield might be source limited in some post-anthesis environments (see MARTINEZ-GARRASCO et al 1988, GRABAU et al 1990, MA et al 1990). SLAFER and MlRALLES Therefore, the analysis of the fate of the plant green tissues after anthesis acquires more interest.…”
Section: Introductionmentioning
confidence: 99%
“…The number of grains m 2 is more associated with grain yield than individual grain weight under different environmental conditions and cultivars (Fischer, 1985;Caldiz & Sarand6n, 1988;Slafer & Andrade, 1989a& 1991Savin & Slafer, 1991), because wheat grain yield is normally sink-limited during the grain filling period (Perez & MartinezCarrasco, 1985;Borghi et al, 1986;Savin & Slafer, 1991); although some source limitation has recently been suggested (Grabau et al, 1990;Ma et al, 1990).…”
Section: Introductionmentioning
confidence: 99%